2020
DOI: 10.3389/fnmol.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Cognitive and Epigenetic Aging: A Retrospective Glance

Abstract: Brain aging is the critical and common factor among several neurodegenerative disorders and dementia. Cellular, biochemical and molecular studies have shown intimate links between oxidative stress and cognitive dysfunction during aging and age-associated neuronal diseases. Brain aging is accompanied by oxidative damage of nuclear as well as mitochondrial DNA, and diminished repair. Recent studies have reported epigenetic alterations during aging of the brain which involves reactive oxygen species (ROS) that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 144 publications
(151 reference statements)
2
74
0
1
Order By: Relevance
“…Factors contributing to OS in the brain include excitotoxicity, depletion of the cellular antioxidant system, high susceptibility to lipid peroxidation, and high oxygen demand [ 41 ]. OS may lead to mitochondrial dysfunction, which further results in the excessive ROS generation and establishes a vicious cycle of OS [ 42 , 43 ]. Moreover, the endoplasmic reticulum (ER), a site for protein folding, also takes part in ROS generation [ 44 ].…”
Section: Pathophysiology Of Brain Disordersmentioning
confidence: 99%
“…Factors contributing to OS in the brain include excitotoxicity, depletion of the cellular antioxidant system, high susceptibility to lipid peroxidation, and high oxygen demand [ 41 ]. OS may lead to mitochondrial dysfunction, which further results in the excessive ROS generation and establishes a vicious cycle of OS [ 42 , 43 ]. Moreover, the endoplasmic reticulum (ER), a site for protein folding, also takes part in ROS generation [ 44 ].…”
Section: Pathophysiology Of Brain Disordersmentioning
confidence: 99%
“…Network pharmacology reveals the complex antiaging mechanism of resveratrol through multitarget, multi-pathway and multi-pathway, and discusses the potential antiaging target of resveratrol, which provides clues and reference directions for the follow-up animal experiments, and lays a good foundation for further discussion of the antiaging pharmacological target and molecular mechanism of resveratrol. Aging is closely related to oxidative stress, endoplasmic reticulum stress and apoptosis (Chen G. et al, 2020;Kandlur et al, 2020). SOD, GSH-Px, CAT, AE, MDA are considered to be related to oxidative stress, and they were found that SOD, GSH-Px, CAT, AE, MDA worked as important parameters reflecting the potential antiaging ability of the body by many previous reasearches (Akbulut et al, 2009;Hui et al, 2020;Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is closely related to oxidative stress, endoplasmic reticulum stress and apoptosis ( Chen G. et al., 2020 ; Kandlur et al., 2020 ). SOD, GSH-Px, CAT, AE, MDA are considered to be related to oxidative stress, and they were found that SOD, GSH-Px, CAT, AE, MDA worked as important parameters reflecting the potential antiaging ability of the body by many previous reasearches ( Akbulut et al., 2009 ; Hui et al., 2020 ; Wang L. et al., 2020 ; Song et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 , 6 ). Numerous studies have highlighted that associations between oxidative stress and brain damage and impaired neuronal plasticity leads to aging-dependent cognitive decline [ 23 , 33 ]. In addition, IL-6 mediates the activation of neuronal NADPH oxidase and cognitive impairment in old mice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%